2014
DOI: 10.1016/b978-0-12-411619-1.00008-2
|View full text |Cite
|
Sign up to set email alerts
|

Brown Adipose Tissue in Humans

Abstract: Research with the aim to translate findings of the beneficial effects induced by brown adipose tissue (BAT) on metabolism, as seen in various non--human experimental systems to also include human metabolism requires tools that accurately measure how BAT influences human metabolism. This review sets out to discuss such techniques, how they can be used, what they can measure and also some of their limitations. The focus is on detection and functional analysis of human BAT and how this can be facilitated by apply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…Thermogenesis in BAT and so-called beige (brite) fat cells may play a role in the pathogenesis of excess adiposity and also provides a target for pharmacologic interventions [58, 59]. Central to the study of human BAT is an array of radiological imaging techniques that can characterize the tissue non-invasively in vivo, namely MRI, positron emission tomography (PET), and CT [60, 61]. …”
Section: Linking Metabolic Activity To Compartment Sizementioning
confidence: 99%
“…Thermogenesis in BAT and so-called beige (brite) fat cells may play a role in the pathogenesis of excess adiposity and also provides a target for pharmacologic interventions [58, 59]. Central to the study of human BAT is an array of radiological imaging techniques that can characterize the tissue non-invasively in vivo, namely MRI, positron emission tomography (PET), and CT [60, 61]. …”
Section: Linking Metabolic Activity To Compartment Sizementioning
confidence: 99%
“…Although it has several limitations, FDG-PET/CT has become the most popular platform for investigating this unique adipose tissue and its physiological relevance to human metabolism, substrate regulation, and obesity. Despite the promise of other imaging methods (Hu and Kan, 2013; Cypess et al, 2014; Borga et al, 2014), it is evident that FDG-PET/CT will continue to have a critical role.…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, three papers were published in the NEJM (Cypess et al, 2009 ; Van Marken Lichtenbelt et al, 2009 ; Virtanen et al, 2009 ) where BAT was unequivocally identified and analyzed in humans, including analysis of genes markers of BAT. During the last 5 years it has been a surge of studies on the possible function of BAT in humans and its regulation by cold, diet, obesity and drugs (Zingaretti et al, 2009 ; Vijgen et al, 2012 , 2013 ; Jespersen et al, 2013 ; Van Der Lans et al, 2013 ; Borga et al, 2014 ; Broeders et al, 2014 ; Chechi et al, 2014 ). Several possibilities have been explored as the induction of brite adipocytes in human adipocytes using BMP7 (Pisani et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%